Duty of care towards visitors what kind of precautions should be taken by the business owner - Md Pauzi, Suria Fadhillah; Mustapha, Musramaini (Universiti Teknologi MARA, Terengganu, 2022)
In relation to business owners, particularly those in the tourism industry, when precautions are given high attention, it will reopen doors to visitors in the endemic of Covid -19. Business owners must strictly adhere to governmentspecified standard operating procedures in ensuring the safety of all involved. This is also to prevent legal repercussions, and therefore, it is imperative that company owners and visitors alike have a thorough understanding of legal rights and responsibilities in case of noncompliance of respective parties.